2022
DOI: 10.2147/vmrr.s366533
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Microbial Therapy Using Antimicrobial Peptides and the CRISPR/Cas9 System

Abstract: The emergence and spread of multidrug-resistant microbes become a serious threat to animal and human health globally because of their less responsiveness to conventional antimicrobial therapy. Multidrug-resistant microbial infection poses higher morbidity and mortality rate with significant economic losses. Currently, antimicrobial peptides and the CRISPR/Cas9 system are explored as alternative therapy to circumvent the challenges of multidrug-resistant organisms. Antimicrobial peptides are small molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 117 publications
0
12
0
Order By: Relevance
“…Other genes and pathways that were frequently studied in the review included those involved in the production of antimicrobial peptides, cytokines, and T-cell receptors. For example, numerous studies found that variations in genes responsible for the production of antimicrobial peptides were associated with disease resistance in various animal species, such as insects, fish, and cattle (21,22,23). Similarly, variations in genes involved in the production of cytokines and T-cell receptors were found to be associated with disease resistance in humans and other animal species.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes and pathways that were frequently studied in the review included those involved in the production of antimicrobial peptides, cytokines, and T-cell receptors. For example, numerous studies found that variations in genes responsible for the production of antimicrobial peptides were associated with disease resistance in various animal species, such as insects, fish, and cattle (21,22,23). Similarly, variations in genes involved in the production of cytokines and T-cell receptors were found to be associated with disease resistance in humans and other animal species.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the previous findings that the peptides Sp-NPFin [ 35 ] from Scylla paramamosain and AS-hepc3 (48–56) [ 36 ] from A. schlegelii effectively inhibited the growth of several multi-drug resistant bacteria. Currently, AMPs are being explored as alternative therapy to tackle infections caused by multidrug-resistant bacteria [ 37 ]. Therefore, the antimicrobial activity of LJ-hep2 (66–86) against multidrug-resistant bacteria will provide more possibilities with regard to the exploration of potential anti-drug resistant bacterial drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Class 1 comprises three types (I, III, and IV) and sixteen subtypes, whereas Class 2 includes three types (II, V, and VI) and seventeen subtypes [ 401 , 402 ]. The Class 1 CRISPR/Cas system takes on interference through the use of a multi-Cas effector protein complex, whereas Class 2 utilises a single effector protein responsible for the identification and cleavage of the target sequence [ 403 ]. Among the type II CRISPR/Cas systems, the most commonly studied effector protein is the DNA endonuclease Cas9 using a specificity-programming guide RNA (gRNA).…”
Section: Qs Pathways Inhibitionmentioning
confidence: 99%